The Journal of European economic history - Banco di Roma (Roma Banco di Roma, 1972)
The Journal of European Economic History it is devoted to the study of the economic history of Europe and of the various European countries, to the study of the impact of the economic history of other continents or countries of other continents upon the history of Europe or of European countries, or viceversa to biographical portraits of important figures in the economic life of every country and time to analysis of problems and aspects which shed light on the economic history of Europe or of its various countries to the theory of economic history, to the European economic historiography.
Is published 3 times a year (Spring, Fall and Winter. Volumes 8-10 are not available at the library. All the articles are freely available and can be searched on www.jeeh.it
Keywords: Economic conditions; ECONOMICS; ECONOMIC HISTORY; ECONOMIC CONDITIONS; EUROPE